Ethical Pitfalls in Scientific Publishing - Mahalakshmy Thulasingam; Bindhya Karthikeyan (International Journal of Advanced Medical and Health Research)
Ethical integrity is crucial for scientific research and publishing. The four ethical principles of research are autonomy, beneficence, nonmaleficence, and justice. These ethical standards must be followed to ensure trust in the scientific inquiry process and to guarantee that the research benefits society or the scientific community. However, the rapid growth and competitive nature of scientific publishing have led to numerous ethical pitfalls. Evidence suggests that a considerable proportion of scientists engaged in questionable research practices while 1 in 50 acknowledged having either fabricated or falsified data at least once in their career. This article explores the common ethical pitfalls in scientific publishing, with respect to authorship issues, plagiarism, data fabrication, challenges in peer review, conflicts of interest, duplicate publication, and predatory journals. The article aims to provide insight into the best practices to maintain scientific integrity and offers recommendations for best practices in scientific publishing.